Utilisation of zakāh and waqf fund in micro-takāful models in Malaysia: an exploratory study - Saʿid Adekunle Mikail; Muhammad Ali Jinnah Ahmad; Salami Saheed Adekunle (ISRA International Journal of Islamic Finance, 2017)
Purpose: This paper aims to investigate the utilisation of both zakāh and waqf fund as external resources to ensure micro-takāful services are delivered to underserved communities in an effective and sustainable manner. It also addresses Sharīʿah issues related to the zakāh- and waqf-based model. Design/methodology/approach: The study is a qualitative-based research. It uses both focus group and content analysis approach to gather primary data and identify and interpret relevant secondary data and Sharīʿah concepts in developing the zakāh- and waqf-based micro-takāful model. Findings: It is discovered throughout the investigation of attributes of beneficiaries of zakāh and waqf institutions as well as micro-takāful scheme that all share commonalities in terms of social securities and socio-economic support to low-income households in societies. The study also finds that the disintegration of zakāh and waqf which form part of the Islamic ecosystem from the micro-takāful model makes it less effective and sustainable. Originality/value: This study appears as a primitive attempt to discuss and develop a zakāh and waqf-based micro-takāful model with reference to Malaysian jurisdiction.
Keywords: 330; Waqf; zakāh; micro-takāful; financial inclusion